Photodynamic Therapy Using Cerenkov and Radioluminescence Light - Spinelli, Antonello E.; Boschi, Federico (Frontiers in Physics, 2021)
In this short review the potential use of Cerenkov radiation and radioluminescence as internal sources for Photodynamic therapy (PDT) is discussed. PDT has been developed over the course of more than 100 years and is based on the induced photo conversion of a drug called photosensitizer (PS) that triggers the production of cytotoxic reactive oxygen species (ROS) leading to the killing of the cells. In order to overcome the problem of light penetration in the tissues, different solutions were proposed in the past. The use of radioisotopes like: 18F, 64Cu, 90Y, 177Lu as internal light sources increase the light fluence at the PS compared to an external source, resulting in a larger cytotoxic effect.